Microproteomics with microfluidic‐based cell sorting: Application to 1000 and 100 immune cells. Issue 13 (4th July 2017) - Kasuga, Kie; Katoh, Yasutake; Nagase, Keisuke; Igarashi, Kazuhiko
Abstract : Ultimately, cell biology seeks to define molecular mechanisms underlying cellular functions. However, heterogeneity within cell populations must be considered for optimal assay design and data interpretation. Although single‐cell analyses are desirable for addressing this issue, practical considerations, including assay sensitivity, limit their broad application. Therefore, omics studies on small numbers of cells in defined subpopulations represent a viable alternative for elucidating cell functions at the molecular level. MS‐based proteomics allows in‐depth proteome exploration, although analyses of small numbers of cells have not been pursued due to loss during the multistep procedure involved. Thus, optimization of the proteomics workflow to facilitate the analysis of rare cells would be useful. Here, we report a microproteomics workflow for limited numbers of immune cells using non‐damaging, microfluidic chip‐based cell sorting and MS‐based proteomics. Samples of 1000 or 100 THP‐1 cells were sorted, and after enzymatic digestion, peptide mixtures were subjected to nano‐LC‐MS analysis. We achieved reasonable proteome coverage from as few as 100‐sorted cells, and the data obtained from 1000‐sorted cells were as comprehensive as those obtained using 1 μg of whole cell lysate. With further refinement, our approach could be useful for studying cell subpopulations or limited samples, such as clinical specimens.